Keindahan dalam Disabilitas: Sebuah Konstruksi Teologi Disabilitas Intelektual - Isabella Novsima Sinulingga (Asosiasi Teolog Indonesia, 2015)
This article challenges conceptions of intellectual disability that view such conditions from the perspective of normalcy. In Indonesia, conversations of theological anthropology still employ a medical model lens, which perceives disability merely as bodily and intellectual impairments, thus failing the standard of